Emerging polymorphisms in falciparum Kelch 13 gene in Northeastern region of India. (December 2016) - Mishra, Neelima; Bharti, Ram; Mallick, Prashant; Singh, Om; Srivastava, Bina; Rana, Roma; Phookan, Sobhan; Gupta, Hardev; Ringwald, Pascal; Valecha, Neena
Abstract Background Recent reports of emergence and spread of artemisinin resistance in the Southeast Asia region, including Myanmar, pose a greater threat to malaria control and elimination in India. Whole genome sequencing studies have associated mutations in the K13 propeller gene (k13 ), PF3D7_1343700 with artemisinin resistance both in vitro and in vivo. The aim of the present study was to find thek13 gene polymorphisms inPlasmodium falciparum parasites from the three sites in the Northeast region of India, bordering Bangladesh and Myanmar. Methods A total of 254 samples collected during 2014–2015 from Tripura, Mizoram and Arunachal Pradesh states in the Northeast region of India were used to obtain the full-lengthk13 gene sequences. Results Three non-synonymous (NS) mutations: two in the propeller region, namely at codon 446 and 578, were observed besides one at codon 189 in the non-propeller region. The treatment outcome was not affected by these mutations at any of the sites. In addition, microsatellite variation in the N-terminus of thek13 protein was observed at all the study sites. Conclusion This is the first study to document the presence of F446I NS mutation in thek13 propeller region from Changlang district, Arunachal Pradesh, a site adjoining the Indo-Myanmar border region, where this mutation is highly prevalent. In addition, NS mutation A578S has been observed only at Lunglei district, Mizoram, a site bordering Bangladesh and K189T mutation with relatively higher frequency in Mizoram and Tripura states. The presence of F446I mutation in a region close to the Myanmar border is notable. Considering the spread of anti-malarial drug resistance from Southeast Asia to the Northeast region of India in the past, there is an urgent need to undertake systematic mapping studies to ascertain the role and extent of this mutation in artemisinin resistance in this region of country.